Hospital pharmacists understanding of available health literacy assessment tools and their perceived barriers for incorporation in patient education - a survey study - Sara Chan; Sean P. Spina; Dalyce M. Zuk; Karen Dahri (BMC, 2020)
Abstract Background Patients with low health literacy experience difficulty in understanding their medications leading to worse health outcomes. Pharmacists need to use formal assessment tools to be able to identify these patients, so they can better tailor their patient education. The objective of the study was to characterize hospital pharmacists understanding of health literacy and their use of screening and counselling strategies before and after completion of an educational module and to identify barriers that hospital pharmacists perceive to exist that prevent them from using health literacy tools. Methods Pharmacists in three health authorities were administered a pre-survey and then given access to an online 11 min educational video. The post-survey was distributed 1 month later. Descriptive statistics were used to quantify survey responses with comparisons made between pre and post responses. The main outcome measure was pharmacists' understanding of health literacy and their current practice related to health literacy. Results There were 131 respondents for the pre-survey and 39 for the post-survey. In the pre-module survey, 84% of pharmacists felt they understood what health literacy was, but only 53% currently assessed patients for their health literacy status and 40% were aware of what strategies to use in low health literacy patients. Lack of time (74%) was the biggest barrier in assessing patients' health literacy. In the post-module survey, 87% felt they understood what health literacy was and 64% incorporated health literacy status evaluation into their clinical practice. The educational module was helpful to the clinical practice of 74% of respondents. Conclusion As health literacy can affect a patient's ability to adhere to their medications it is important for pharmacists to assess this in their patients. While pharmacists self-reported a high degree of understanding of health literacy, they are not regularly assessing their patients' health literacy status and are unaware of what strategies to use for low literacy patients.